Peculiarities of measurement uncertainty evaluation at calibrating a ring gauge - Zakharov, I.; Botsiura, O.; Diakov, D.; Świsulski, D. (My University, 2023)
Example S13 from EA-4/02 M:2013 “Calibration of a ring gauge with a nominal diameter of 90 mm” is analyzed. The report uses the kurtosis method and the law of propagation of expanded uncertainty developed by the authors to the expanded uncertainty evaluation. It is shown that the introduction of a coaxiality correction for the ring gauge and the measuring axis of the comparator leads to the need to estimate its standard measurement uncertainty using the second-order terms of the Taylor series and taking into account the kurtosis of input quantities using the method of partial increments. A good agreement between the results obtained by applying the described procedure and the results obtained by the Monte Carlo method is shown.
Keywords: measurement uncertainty, Kurtosis method, calibration, ring gauge